2017
DOI: 10.1111/ajo.12576
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum intervention rates and perinatal outcomes following induction of labour compared to expectant management at term from an Australian perinatal centre

Abstract: Background: Induction of labor (IOL) is a common obstetric intervention, yet its impact on intervention rates and perinatal outcomes is conflicting. Aims:To evaluate the impact of IOL on intrapartum intervention rates and perinatal outcomes in women with singleton pregnancies at term. Results: Of the final cohort (44 698 women), 64.4% had expectant management and 35.6% had IOL. Multivariate analyses showed that IOL was associated with lower odds of spontaneous vaginal delivery from ≥37 weeks gestation. The ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 22 publications
0
21
1
Order By: Relevance
“…It is possible that the missing data is a reflection of unclear documentation in the woman’s pregnancy records of the reason why she was booked for IOL by the physician when the procedure was decided or the possibility that women with missing indication could have been induced for a reason that is not in line with the local evidence-based policy. Although lack of documented reason for induction has been demonstrated in several studies, the rate we report is higher than those reported from South America (44%),30 Australia (16.1%),31 and the United States (7.9%) 9. However, it is important to note that some of these studies categorized women with no documented reason for induction as elective (no medical indication) inductions 8,9,30.…”
Section: Strengths and Limitationscontrasting
confidence: 71%
“…It is possible that the missing data is a reflection of unclear documentation in the woman’s pregnancy records of the reason why she was booked for IOL by the physician when the procedure was decided or the possibility that women with missing indication could have been induced for a reason that is not in line with the local evidence-based policy. Although lack of documented reason for induction has been demonstrated in several studies, the rate we report is higher than those reported from South America (44%),30 Australia (16.1%),31 and the United States (7.9%) 9. However, it is important to note that some of these studies categorized women with no documented reason for induction as elective (no medical indication) inductions 8,9,30.…”
Section: Strengths and Limitationscontrasting
confidence: 71%
“…Observational studies comparing IOL with expectant management from outside the USA are scant. In a single‐center retrospective cohort study from Australia, IOL was associated with increased risk of emergency cesarean for intrapartum fetal distress 19 . A Danish birth registry‐based study indicated increased risk of cesarean delivery following IOL at 37 and 38 weeks, whereas there was no significant difference from gestation week 39 and after in either nulliparous or parous women 20 .…”
Section: Discussionmentioning
confidence: 99%
“…We also did not include differences of induction of labour rates between the two cohorts and this might have potentially influenced the outcomes. The influence of induction of labour on caesarean section rates and neonatal outcomes are however conflicting, with some studies [ 32 ] demonstrating no difference in either operative birth rates and others[ 33 ] suggesting an increase in intervention in the induction cohort. Other possible residual confounders including maternal educational level, number of antenatal visits, model of antenatal care, alcohol intake, or other barriers that may have influenced a woman’s experience in accessing care, were not measured.…”
Section: Discussionmentioning
confidence: 99%